Multifunctionality in English corpora, language and academic literacy pedagogy - Yin, Zihan; Vine, Elaine W. (Routledge, 2022)
This edited volume provides detailed analyses of multifunctional forms in English and hands-on approaches to exemplifying relevant implications and useful applications to language and literacy educators in TESOL, ESL/EFL/EAL, academic literacies and postgraduate coursework and research students in applied linguistics and Education. The content covers: the multifunctionality of utterances in spoken and multimodal corpora, the multifunctionality of linguistic creativity in different genres, multifunctional pronouns in hard and soft sciences and professional discourse in the university and secondary school contexts, comparison of the multifunctionality of verbs between ESL textbooks and native written and spoken English corpora and between ESL and L1 university students in writing a particular genre, comparison of the multifunctionality of discourse markers between different registers and between L1 and L2 English speakers, and multifunctional metadiscourse markers in different disciplines and paradigms. With detailed analysis of authentic corpus data representing different varieties of English, specialised use in different contexts and disciplines and practical teaching and learning applications, the volume bridges theory and practice, providing a creatively designed resource for students, educators and researchers looking to understand multifunctional forms in English"-- Provided by publisher.